#ThisIsMeChallenge and Music for Empowerment of Marginalized Groups on TikTok - Vizcaíno-Verdú, Arantxa (2022)
Media convergence is generating many collective performances on social media, where the rise of short-form videos has created a new opportunity for the empowerment of society on online platforms. In this context, TikTok appears as an application for creative expression through music clips and lip-syncs. Through the #ThisIsMeChallenge hashtag, which introduces the musical theme of The Greatest Showman film, we analyze a new online practice within messages from traditionally marginalized groups throughout individual and collective life events. In order to understand TikTok as a music venue for social empowerment, we conducted a quantitative content analysis of 100 TikTok posts under the hashtag, and an artificial intelligence sentiment analysis across 8,877 comments. The results show a wide range of performance work that addresses issues of gender, sexual orientation, racial discrimination, and other types of current hate speech. In short, we conclude that TikTok has become a platform that seems to motivate activism and empowerment of marginalized groups through music frameworks that challenge social discrimination.